Analisis Kinerja Simpang Bersinyal Pusat Grosir Cililitan (PGC) Jalan Dewi Sartika - Jalan Raya Bogor Dengan Metode PKJI 2014 Dan Pemodelan Menggunakan PTV VISSIM: Performance Analysis Of Cililitan Wholesale Center (PGC) Bogor Street –Dewi Sartika Street East Jakarta With The 2014 PKJI Method And Modeling Using PTV VISSIM - Azia Novia Riza; Adita Utami; Asep Yayat Nurhidayat (Media Ilmiah Teknik Sipil, 2023)
Pusat Grosir Cililitan (PGC) signalized intersection is one of the 67 traffic-prone locations located in DKI Jakarta Province, this is because in this intersection there are many business centers in Cililitan such as factories, malls, SMEs, markets, street vendors, and schools that operate which causes poor interchange performance. Poor interchange performance leads to queue length, delays, fuel wastage and time loss due to congestion. This research was conducted to analyze and optimize intersections using the PKJI 2014 method and the Student version of PTV Vissim Software. Based on the results of the study, the largest saturation degree (DS) value was obtained, namely 2,298 skr / hour, queue length (QL) of 130.84 meters, the largest average deviation delay (Dsimpang) of 361.65 s / skr. Meanwhile, the results of one of the optimizations of the intersection provide an alternative to the optimization of the interchange performance by changing the previously 4-phase phase to 2-phase and eliminating the movement of the right turn, and a decrease in delay to 48.85 seconds / skr and a change in the interchange performance category from LoS F to LoS E.